Modifikasi Ventilasi pada Tutup Stup Koloni Lebah Madu (Apis Mellifera) Terhadap Produksi Propolis - Ramadhan, E.; Siregar, H. C. H.; Kuntadi, Kuntadi (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
This research aims to determine the best ventilation modification to produce propolis. The study was conducted at the foot of Mount Tampomas, Sumedang, West Java, in 5 weeks from July to August 2013. The material used were 15 hives of Apis mellifera honey bee colony with population 16 000 – 20 000 bees. The 15 colonies were randomly divided into 3 levels treatment of ventilation size on the lid nest, that were no ventilation as control treatment (A), 50 cm2 (B), and 100 cm2 (C) ventilation holes. Propolis trap was installed in each hive. The experimental design used was completely randomized design followed by T-test. The results showed that ventilation size was not significantly affected propolis production but significantly affected honey production.   Honey production in C treatment was significantly higher. In general the best treatment hive cap to produced propolis and honey are C treatment with the highest average weight of propolis and honey for 5 weeks was 16.4±6.98 g and 3101.6± 581.5 g also have a big end population